THE EFFECT OF SOIL WATER CONTENT AND GAMAL BOKASHI ON VEGETATIVE GROWTH OF SWEET CORN (ZEA MAYS SACCARATA) - Nur Afifah Usman; Anthon Monde; Uswah Hasanah (AGROLAND: The Agricultural Sciences Journal, 2017)
This research aimed to get the moisture content and dose of bokashi gamal accordance with the vegetative growth of the sweet corn  plant (Zea mays saccarata) and the benefit of this study was to provide the information on the effects of agriculture on groundwater levels and bokashi gamal to plants. The research design using factorial completely randomized design. The first factor bokashi gliricidia with 3 levels of treatment was without bokashi gamal (B0), bokashi gamal 20 t.ha-1(B20), and bokashi gamal 40 t.ha-1 (B40). The second factor levels with 3 levels of water treatments, namely, water content 50% field capacity (K50), the water content of 75% field capacity (K75), and water content 100% of field capacity (K100). Treatment was repeated three times to obtain 27 experimental units. Data analyzed by analysis of variance according to the design used and conducted a further test using Honestly Significant Difference (HSD). The results showed the interaction between water content and Bokashi Gamal significantly affected the vegetative growth of the plants sweet corn. The water content of 50-75% and gamal bokashi 20-40 t.ha-1gave the best to plant vegetative growth of sweet corn.